Development of a folding arm on an articulated mobile robot for plant disaster prevention. (17th January 2020) - Matsumoto, Nobutaka; Tanaka, Motoyasu; Nakajima, Mizuki; Fujita, Masahiro; Tadakuma, Kenjiro
Abstract: In this work, we develop a folding arm on an articulated mobile robot to inspect an industrial plant. The design targets of the arm, its operations, measurement ability, and mobility, were set for the task of inspecting an industrial plant. To accomplish the targets, we designed the folding arm considering both accessibility to high locations and the mobility of the articulated mobile robot to which it is attached. The arm has links, joints, dummy wheels, and sensors and enables the robot to which it is attached to manipulate objects, e.g. rotating valves, opening a door, or inspecting by accessing high locations. In addition, changing the posture of the arm and touching the dummy wheel in the arm to the surrounding terrain can reduce any negative effect of the arm on the robot's mobility when it encounters narrow spaces, stairs, steps, and trenches. The arm is controlled as a six degrees-of-freedom manipulator without redundancy by an operator who directly sets two joint angles. The effectiveness of the developed arm was demonstrated not only through experiments in a laboratory but also in a field test at the Plant Disaster Prevention Challenge of the World Robot Summit 2018. GRAPHICAL ABSTRACT: